Elderly woman with acute necrotizing ulcerative gingivitis (Vincent disease): a case report - Larisa I. Glebova; Ekaterina V. Zadionchenko (LLC "MEDIAFORMAT", 2021)
Acute necrotizing ulcerative gingivitis (Vincent disease) is an inflammatory disease also known as ulcerative gingivitis, necrotizing ulcerative gingivitis, fusospirochetal stomatitis, Plaut-Vincent stomatitis, and trench mouth. In case of gingival lesions the Vincent gingivitis is diagnosed; in case of simultaneous lesions of the gingivae and oral mucosa the disease is considered the Vincent stomatitis, and in case of pharyngeal tonsil it is considered the Vincent angina. Rare case of the elderly woman with the disease involving gingival and palatal mucosa is reported. Main causes of the disease are discussed, differential diagnoses are listed, and preventive measures are outlined